A Practical Guide to Managing Systemic Financial Crises : A Review of Approaches Taken in Indonesia, The Republic of Korea, and Thailand - Scott, David (World Bank, Washington, D.C., 2013)
The author examines experiences in Indonesia, the Republic of Korea, and Thailand in confronting systemic financial crises during the 1990s. He draws on the knowledge and experience of World Bank staff who managed the Bank's financial and technical assistance to those countries. In reviewing the principal actions taken by the governments to resolve the crises, the author describes key challenges that governments face in tackling crises, defines basic guidelines and principles for responding to those challenges, and proposes steps to improve the ability of governments to deal with crises when they do occur, as well as to mitigate the risk of crises in the first place. The author addresses matters such as the provision of liquidity, institutional arrangements for crisis resolution, use of public funds, diagnosis of problems, resolution, recapitalization, restructuring of banks, privatization of banks, restructuring of troubled debt, and use of asset management companies. He goes on to develop the conceptual underpinnings for two fundamental improvements in crisis management practices, one to develop an explicit, comprehensive crisis resolution strategy, and the second to link the provision of support to banks explicitly to the actual outcomes of troubled debt restructuring. A common theme in both is to maximize the impact of public funds used in crisis resolution. Finally the author identifies steps that governments can take to mitigate the risk of crisis and be better prepared to deal with shocks should they occur, including the use of contingency planning in the context of liquidity management and intervention in weak banks.